The Importance of Job Demands and Supports: Promoting Retention Among Child Welfare Workers - Radey, Melissa (Child Adolesc Social Work J, 2021)
Child welfare workers typically face strict deadlines, limited training periods, high caseloads, and understaffing. These high-demand positions often coupled with few organizational or supervisory supports contribute to decreased worker well-being and low retention. Informed by the Job Demands-Resources model, we examined common demand-resource sub-groups among recently-hired child welfare workers and how sub-group membership contributed to agency retention. This study used data from the Florida Study of Professionals for Safe Families (FSPSF), a four-year, longitudinal cohort study of child welfare workers hired in 2015–16 (n = 912). We used a three-step Latent Profile Analysis (LPA) with logistic regression to identify profiles of workers based on demand and support levels at 6 months to predict agency retention 12 months later. Findings resulted in five profiles: floundering, surviving through supervisor, surviving through role, surviving through supports, and thriving. Profile distributions indicated both demands and supports were independently important for retention. Each profile had higher odds of staying at the agency compared to the floundering profile, those floundering in role and support (ORs = 2.08–7.68). Those in the thriving profile, thriving in role and support, had higher odds of staying when compared to each other profile (ORs = 2.12–7.68). Findings identify that demands and supports operate in an additive way to promote retention and suggest that agencies can address individual aspects of workers’ role and support challenges to improve retention without requiring a single approach to combat workload and environment simultaneously.